Analisis Pemahaman Konsep Siswa Kelas XI IPA SMAN 1 Malang Pada Topik Bentuk Molekul - Sabekti, Ardi Widhia; Widarti, Hayuni Retno; , Mahmudi (Program Studi Pendidikan Kimia, Fakultas Keguruan dan Ilmu Pendidikan Universitas Maritim Raja Ali Haji, 2014)
Analisis Pemahaman Konsep Siswa Kelas XI IPA SMAN 1 Malang  pada Topik Bentuk Molekul. The purpose of research is to identify: (1) studentâs understanding level about molecular shape, (2) studentâs misconception about molecular shape, and (3) studentâs ability to fulfill the problems in Indonesian language and English language about molecular shape. Research uses quantitative descriptive design. Populations are 11th Grade Science Students of SMAN 1 Malang in 2010/2011 academic year that consist of 6 classes. Samples are students of 11th Grade Science 1, 3, and 4. Sampling technique is simple random sampling, which takes the sample member randomly without concern in populationâs strata. Instrument in research is 20 problems objective test; consist of 10 problems in Indonesian language and 10 problems in English language. Instrumentâs reliability is 0.73 and the validity is 98.3%. Every problem has 5 alternative answers that are supported by reason of answer and interview result. Research result indicates that (1) Studentâs understanding level about molecular shape is medium (54.5%). If regarded from aspects those are measured, studentâs understanding about bond angle is medium (53.7%); studentsâ understanding about stability of molecule based on lone pair placement is medium (54.9%); prediction of molecular shape is high (60.1%); studentsâ understanding about the polarity of molecule is medium (40.7%); hybrid orbital is high (70.6%); and studentsâ understanding about hybridization process is medium (46.7%). (2) The studentâs misconceptions are: (a) fewer amount of bonding pair, the value of bond angle is bigger (3.9%); (b) double bond donate two bonding pair (2.9%); (c) lone pair is not has effect in molecular shape prediction (25.5%). (3) Studentâs ability to fulfill the problems in Indonesian language (55.78%) is equal with studentâs ability to fulfill the problems in English language (56.07%).